The Terrible Truth about Third Grade - Leslie McGuire (Cessnock, NSW, Australia Lioncrest Pty Ltd, 1992)
Bored with school, Jane, a precocious reader, neglects her homework and alienates her classmates by making up incredible stories about herself until her teacher, Mrs. Sims, finds a creative solution.
Keywords: Fiction